Psychological Distress Among South African Civil Engineers - Aldera, Daniela (Department of Construction Economics and Management, 2023)
The construction industry is notoriously associated with work-related stress and time pressures. The repercussions of stress are experienced by both employees and organisations. The focus on the mental health and overall well-being of workers has been more prevalent in the public consciousness in recent years. Research focused on psychological distress has become popular in recent studies due to its close relationship with workload issues and worklife conflict among employees. This study investigates the determinants of psychological distress among South African civil engineers. Specifically, the occurrence of availability of resources and communication, job control, (un)balanced workload, work relationships, job security and change, and working conditions are studied to determine the association between these factors and psychological distress. The research method comprised a critical review of the existing literature on psychological distress, workplace stressors, and the distribution of an online survey questionnaire to civil engineer members of the South African Institution of Civil Engineering (SAICE). Using the 142 survey responses, multiple regression analysis was employed to assess the relationship between availability of resources and communication, job control, (un)balanced workload, work relationships, job security and working conditions, and psychological health. The results indicate that psychological distress is determined by all the workplace stressors, except job control. Interventions aimed at reducing psychological distress among civil engineers in South Africa should focus on the development and promotion of mental health programmes and general support to employees by organisations.